Utility of immune monitoring in heart transplant recipients on everolimus‐based immune suppression. (21st March 2014) - Ben Gal, Tuvia; Israeli, Moshe; Yaari, Victoria; Hasdai, David; Matz, Israel; Yussim, Alexander; Battler, Alexander; Klein, Tirza; Medalion, Benjamin
Abstract Background Everolimus provides effective immune suppression (IS) after heart transplant (HTx). Its pharmacologic properties differentiate everolimus from other IS drugs. A non‐invasive immune monitoring (IM) assay test appears to predict the immune state in HTx recipients on standard calcineurin‐inhibitor‐based IS. The utility of IM in HTx recipients on everolimus‐based IS was evaluated. Methods Between June 2005 and June 2011, 34 adult HTx recipients followed up at our center received everolimus and had 381 IM assays that were performed at six months to 16‐yr post‐transplant. Results of the IM assay were correlated with infection and rejection episodes that occurred during the IM testing. Results In the everolimus‐based IS group, there were 18 infectious episodes and four rejection episodes. The average IM score was significantly lower during infection than at steady state (188 ± 122 vs. 338 ± 137 ng/mL ATP, p < 0.001) and not significantly different during rejection when compared with steady state (430 ± 132 vs. 338 ± 137 ng/mL ATP, p = 0.5). Conclusions The non‐invasive IM assay predicts infectious risk in HTx recipients on everolimus‐based IS. Its inconclusive association with rejection was probably due to the small number of rejections. Serial longitudinal IM may allow proper adjustment of everolimus doses.